Use of Potentiometric Fluorophores in the Measurement of Mitochondrial Reactive Oxygen Species - Polster, Brian M. (Methods Enzymol, 2014)
Mitochondrial reactive oxygen species (ROS) are implicated in signal transduction, inflammation, neurodegenerative disorders, and normal aging. Net ROS release by isolated brain mitochondria derived from a mixture of neurons and glia is readily quantified using fluorescent dyes. Measuring intracellular ROS in intact neurons or glia and assigning the origin to mitochondria are far more difficult. In recent years, the protonmotive force crucial to mitochondrial function has been exploited to target a variety of compounds to the highly negative mitochondrial matrix using the lipophilic triphenylphosphonium cation (TPP(+)) as a “delivery” conjugate. Among these, MitoSOX Red, also called mito-hydroethidine or mitodihydroethidium, is prevalently used for mitochondrial ROS estimation. Although the TPP(+) moiety of MitoSOX enables the many-fold accumulation of ROS-sensitive hydroethidine in the mitochondrial matrix, the membrane potential sensitivity conferred by TPP(+) creates a daunting set of challenges not often considered in the application of this dye. This chapter provides recommendations and cautionary notes on the use of potentiometric fluorescent indicators for the approximation of mitochondrial ROS in live neurons, with principles that can be extrapolated to non-neuronal cell types. It is concluded that mitochondrial membrane potential changes render accurate estimation of mitochondrial ROS using MitoSOX difficult to impossible. Consequently, knowledge of mitochondrial membrane potential is essential to the application of potentiometric fluorophores for the measurement of intramitochondrial ROS.